Assessing children ́s perceptions of writing in EFL based on the process approach - Melgarejo Melgarejo, Daniel Albeiro (Colombian Applied Linguistics Journal, 2010)
This action research study focused on the analysis of children’s perceptions of writing in English as a Foreign Language (EFL) and was grounded in the theory of the process approach. This approach was considered in view of students’ negative perceptions on writing, their lack of motivation to write, and their poor writing skills in EFL. Therefore, a number of cognitive processes such as planning, translating thought into text and revising were included. The children who took part in the study were between 9 and 13 years old and were in the intermediate English level at a language institute in a public university in Bogota. The aim was to consider such perceptions and see how they evolved during the implementation of workshops based on the stages proposed by the process approach. Furthermore, in addition to an analysis of student perceptions, a secondary aim was to motivate students to write and to help improve their written productions. The data gathered through portfolios, conferences, journals and logs showed that the students changed their prior negative perceptions on writing in EFL, felt motivated to carry out writing tasks, and became more self-aware of their writing practices.